Encyclopedia of Human Relationships 2009
DOI: 10.4135/9781412958479.n25
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and Sexual Assault

Abstract: Conservative estimates of sexual assault prevalence suggest that 25 percent of American women have experienced sexual assault, including rape. Approximately one-half of those cases involve alcohol consumption by the perpetrator, victim, or both. Alcohol contributes to sexual assault through multiple pathways, often exacerbating existing risk factors. Beliefs about alcohol's effects on sexual and aggressive behavior, stereotypes about drinking women, and alcohol's effects on cognitive and motor skills contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(47 citation statements)
references
References 19 publications
1
43
0
3
Order By: Relevance
“…Alcohol does though have a disinhibiting role in sexual assaults, it reduces inhibitions, clouds judgements and impairs ability to interpret cues [91]. As lack of reporting causes a problem in identifying the precise incidence of alcohol being associated with rape, the estimates are similar to violent crime in general and range between 34-74% [92]. The role of alcohol is complex [96].…”
Section: Alcohol and Sexual Violencementioning
confidence: 50%
See 1 more Smart Citation
“…Alcohol does though have a disinhibiting role in sexual assaults, it reduces inhibitions, clouds judgements and impairs ability to interpret cues [91]. As lack of reporting causes a problem in identifying the precise incidence of alcohol being associated with rape, the estimates are similar to violent crime in general and range between 34-74% [92]. The role of alcohol is complex [96].…”
Section: Alcohol and Sexual Violencementioning
confidence: 50%
“…Conservative estimates suggest that at least 25 percent of American women have been assaulted in adolescence or adulthood and that 18 percent have been raped. Furthermore, at least 20 percent of American men report having perpetrated sexual assault and 5 percent report having committed rape [92].…”
Section: Wakefulness and Sexual Violencementioning
confidence: 99%
“…An alternative explanation to the gender findings is the possibility that the social situations around which sexual assault occurs differ for men and women. Women may be more likely fall victim to sexual assault when they are in social situations that encourage both drinking and sexual pursuit, like bars or parties (Abbey et al, 2001), and perhaps the environments for victimization of men differ. Additionally, whether differences exist in the social situations and environments that lead to intimate partner violence against men who have sex with men versus heterosexual men is unclear from our study.…”
Section: Discussionmentioning
confidence: 99%
“…High rates of chronic drug and alcohol abuse have been described among both assailants and victims of violent crimes, sexual assault, and intimate partner violence (Abbey, Zawacki, Buck, Clinton, & McAuslan, 2001;Chermack & Blow, 2002;Cunradi, Caetano, Clark, & Schafer, 1999;Cunradi, Caetano, & Schafer, 2002;Kilpatrick, Acierno, Resnick, Saunders, & Best, 1997;Lown & Vega, 2001;Rivara et al, 1997;Sharps, Campbell, Campbell, Gary, & Webster, 2001;Zavala & French, 2003). Other work has also shown that assailants and victims of sexual and physical violence are often substance using at the time of the event (Caetano, Schafer, & Cunradi, 2001;Chermack & Blow, 2002;Kantor & Straus, 1989;Mohler-Kuo, Dowdall, Koss, & Wechsler, 2004;Thompson & Kingree, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation